Epiphytic microalgae community as aquatic bioindicator in Brantas River, East Java, Indonesia - Sulastri Arsad; Khabib Taufiq Putra; Nurul Latifah; Miftahul Khair Kadim; Muhammad Musa (Society for Indonesian Biodiversity, 2021)
Abstract. Arsad S, Putra KT, Latifah N, Kadim MK, Musa M. 2021. Epiphytic microalgae community as aquatic bioindicator in Brantas River, East Java, Indonesia. Biodiversitas 22: 2961-2971. One way to monitor water quality is by using biological indicators, namely epiphytic microalgae (periphyton). This study aims to analyze the epiphytic periphyton community structure and analyze the river health status using a saprobic index. The research location was in the Brantas River, Blitar District, East Java, Indonesia. The method used was a survey with sampling at three sites based on the purposive sampling technique. Periphyton samples were taken using the quadrant transect (5x5 cm²) method and then identified using the Lackey Drop Micro transect Counting Method. The results show that the periphyton community structure is in balance, and there are six divisions of 59 different genera. The six divisions found are Bacillariophyta, Cyanophyta, Chlorophyta, Charophyta, Ochrophyta, and Rhodophyta. The most identified genus is from the Bacillariophyta Division with 28 genera, while the least identified genus is the Rhodophyta division with 1 genus. The abundance ??ranges from 242,800-1,229,174 cells. cm-2, the relative abundance index ??of periphyton ranges from 3-60% (site 1), 9-57% (site 2), 1-62% (site 3), the diversity index ranges from 1.212-2.617 (moderate), the uniformity index ranges from 0.307-2.151 (high), the dominance index ranges from 0.105-0.549 (moderate), and the saprobic index ranges from-0.18 to 0.55. Moreover, supporting water quality parameters are still optimal, except for ammonia and total organic matter parameters that exceed the quality standard. Based on the saprobic value obtained, the water quality of the Brantas River in Tawangrejo Village can be classified into the category of ?/?-mesosaprobic to ?-mesosaprobic saprobic levels with mild to moderate levels of pollution.